The Encyclopedia of Sexism in American Films - Murguía, Salvador Jiménez; Dymond, Erica Joan; Fennelly, Kristina (Rowman & Littlefield Publishers, 2019)
The treatment—and mistreatment—of women throughout history continues to be a necessary topic of discussion, in order for progress to be made and equality to be achieved. While current articles and books expose troubling truths of the gender divide, modern cinema continues to provide problematic depictions of such behavior—with a few heartening exceptions. The Encyclopedia of Sexism in American Films closely examines the many, pervasive forms of sexism in contemporary productions—from clueless comedies to superhero blockbusters. In more than 130 entries, this volume explores a number of cinematic grievances including: the objectification of women’s bodies the limited character types available for female performers the lack of sexual diversity on the screen the limited range of desirable traits for female performers the use of gratuitous sex the narrow focus on heteronormative depictions of courtship and romance The films discussed here include As Good as It Gets (1999), Beauty and The Beast (2017), The Devil Wears Prada (2006), Do the Right Thing (1989), Easy A (2010), The Forty-Year-Old Virgin (2005), Hidden Figures (2016), Lost in Translation (2003), Mulholland Drive (2001), Showgirls (1995), The Silence of the Lambs (1991), Star Wars (1977), Thelma & Louise (1991), Tootsie (1982), The Witches of Eastwick (1987), and 9 to 5 (1980). By digging deeply into more insidious forms of sexual/gender discrimination, this book illuminates one more aspect of women’s lives that deserves to be understood. Offering insights and analysis from more than fifty contributors, The Encyclopedia of Sexism in American Films will appeal to scholars of cinema, gender studies, women’s studies, and cultural history.